DIGITAL TRANSFORMATION IN ISLAMIC EDUCATION: INTEGRATING AI AND MACHINE LEARNING FOR PERSONALIZED LEARNING IN MADRASAH - Hayati, Naila; Ushalli, Eskarni (Journal of Scientech Research and Development, 2024)
This study examines the potential of digital transformation in Islamic education, focusing on the integration of artificial intelligence (AI) and machine learning (ML) to enhance personalized learning in Madrasah. Islamic educational institutions have traditionally followed structured curricula, but the evolving needs of 21st-century learners demand more adaptive and personalized approaches. AI and ML technologies offer significant opportunities to tailor educational experiences to individual student needs, facilitating improved engagement and learning outcomes. This paper reviews existing literature on the application of AI in education and explores how these technologies can be adapted to the specific context of Madrasah. Challenges, including technical infrastructure, teacher preparedness, and ethical considerations in AI implementation, are also addressed. The findings suggest that while AI integration presents substantial benefits, it requires careful planning and resource allocation to ensure successful implementation. This review contributes to a better understanding of how AI can transform Islamic education through personalized learning. Recommendations for future research are provided to guide the practical application of these technologies in religious education settings.